2020
DOI: 10.3390/plants9121698
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Changes of Broussonetia papyrifera Seedlings in Cadmium Contaminated Soil

Abstract: Broussonetia papyrifera is a widely distributed economic tree species, and it is also a pioneer species in adverse environments. In order to investigate the growth and adaptation mechanism of B. papyrifera under cadmium (Cd) contaminated soil, potted experiments were used with six-month treatments to study Cd enrichment and the transportation, morphological and physiological characteristics of B. papyrifera tissues. The results showed that Cd mainly accumulated in the root when the Cd concentration was high (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 82 publications
0
18
2
Order By: Relevance
“…The study revealed Broussonetia papyrifera, Musanga cecropioides, Celtis mildbraedii, Nesogordonia papaverifera, and Celtis zenkeri to be more dominant in the recently-logged forest plots compared to the loggedover and unlogged-forest areas. B. papyrifera, M. cecropioides, and C. zenkeri are pioneer species that are widely distributed in adverse environments (Zhang et al, 2020). In fact, B. papyrifera and M. cecropioides are indicator species and the occurrence of which signifies disturbance and degradation of a particular ecosystem (Cazzolla Gatti et al, 2017).…”
Section: Species Dominance In Logged and Unlogged Forest Plotsmentioning
confidence: 99%
“…The study revealed Broussonetia papyrifera, Musanga cecropioides, Celtis mildbraedii, Nesogordonia papaverifera, and Celtis zenkeri to be more dominant in the recently-logged forest plots compared to the loggedover and unlogged-forest areas. B. papyrifera, M. cecropioides, and C. zenkeri are pioneer species that are widely distributed in adverse environments (Zhang et al, 2020). In fact, B. papyrifera and M. cecropioides are indicator species and the occurrence of which signifies disturbance and degradation of a particular ecosystem (Cazzolla Gatti et al, 2017).…”
Section: Species Dominance In Logged and Unlogged Forest Plotsmentioning
confidence: 99%
“…Miers Ethanol extract of aerial parts protected dopaminergic neurons and reduced iron accumulation in brain Parkinsonism Kosaraju et al, 2014 Ethanol extract of stem improved COX-2, iNOS, ICAM-1, pro-inflammatory cytokines levels in asthma induced mice Lung related complications Tiwari et al, 2014 Consumption of stem extract modulates changes in kidney chondroitin sulphate or dermatan sulphate in diabetes induced animal model Kidney complications Joladarashi et al, 2012 Aqueous extract of stem and leaves improved superoxide dismutase, catalase, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and acid phosphatase level Liver related problem Sharma and Pandey, 2010 Moraceae Broussonetia papyrifera (L.) L'Her. ex Vent Root bark extract showed hepatoprotective effect by prevention of hepatic steatosis in high fat diet treated mice Liver related problem Lee et al, 2020 Traditionally the fruit extract used to treat various ailments related to heart Cardiac complications Zhang et al, 2020 c The plant along with L. japonica reduced in-vivo septic inflammation and TNF-α, IFN-g, IL-1b levels and also inhibited cell recruitment in bronchoalveolar lavage fluid Lung related complications Ko et al, 2013 Chloroform extract of twigs possessed improved Parkinson's condition in mushroom tyrosinase Parkinsonism Zheng et al, 2008 Morus alba L. Ethanol extract of root bark prevented endothelial dysfunction in rat aorta Cardiac complications Panth et al, 2018 Root bark extract improved depression like behaviour condition in high fat diet treated rats and also reduced brain-derived neurotrophic factor expression and extracellular signal-regulated kinase phosphorylation Mental Problem Ye et al, 2016 Flavonoid fraction from leaves showed potent nephroprotective activity by reducing the blood urea nitrogen and creatinine concentration induced in cisplatin treated rats Kidney complications Nematbakhsh et al, 2013 …”
Section: Herbal Formulae From Different Traditional Systems Of Medicinementioning
confidence: 99%
“…After drying and sieving the soil samples, the physicochemical properties were analyzed and the heavy metal content was determined. Soil moisture content is determined by drying the soil to a constant weight [49]. The organic carbon (SOC) was determined by potassium dichromate hydration heating method [50], the total nitrogen (TN) was determined by Kjeldahl method [50], and the total phosphorus (TP) was determined by molybdenum antimony colorimetry [51,52]; the content of heavy metals (Cu and Cd) was determined by the atomic adsorption spectrophotometer (AAS) after digestion with a mixture of HNO3-HCL-HCLO4 [52,53].…”
Section: Determination Of Soil Physicochemical Properties and Heavy Metal Contentmentioning
confidence: 99%